Make-or-buy decisions and the manipulability of performance measures - Fredrik N. G. Andersson (Lund University, School of Economics and Management, Department of Economics, 2009)
The make-or-buy decision is analyzed in a simple framework combining contractual incompleteness with the existence of imperfect but contractible performance measures. Contractual incompleteness gives rise to two regimes, identified with make and buy. The performance measure on which comprehensive contracts can be written is imperfect in the sense of being subject to manipulation. The main result is that the impact – or "externality" – of manipulation on true performance is key; a positive (negative) such externality favors make (buy).
Keywords: D23; L22; L24; 330; make-or-buy decision; manipulation; outsourcing